Lund -Mackay staging for rhinosinusitis, correlation between computed tomography scan score and intraoperative findings - Qais Aljfout; Hesham Rashdan; Abdullah Maita; Mohammad Saraireh; Abdelrazzag Alrefo; Mohammad Hiari (International Journal of Medical Research and Review, 2016)
Objective: We have conducted this study to evaluate the accuracy of Lund – Mackay scoring system for rhinosinusitis with regards to time lag between dates of both CT scan and operation.Methods: A total of 120 rhinosinusitis patients, divided into three groups according to time lag between date of performing sinuses CT scan and date of surgery. Group A, the time lag was more than 8 weeks, in group B the time lag was 2-8 weeks, and group C, the time lag was less than two weeks. All patients underwent endoscopic sinus surgery; rhinosinusitis was staged using Lund – Mackay system and compared intraoperative findings using the same scoring system.Results: There was a significant difference in staging score in group A, and in group B although the difference was not statistically significant, it was scientifically noticed, in group C there was no difference between the preoperative and intraoperative scores.Conclusion: The correlation between Lund – Mackay staging and intraoperative finding in endoscopic sinus surgery depends on the time lag between scan date and surgery date, the shorter the time lag the better the correlation.